Generic and oral quality of life is affected by oral mucosal diseases - Liu Li-Jun; Xiao Wen; He Qing-Bo; Jiang Wei-Wen (BMC, 2012)
Abstract Background The generic and oral health-related quality of life (QoL) has provided opportunity for investigation of the interrelations among generic health, oral health, and related outcomes. The purpose of this study was to identify the generic and oral QoL in the patients with oral mucosal disease (OMD). Methods Five hundred and thirty-eight OMDs were recruited in this study. The instruments applied were Chinese version of the 36-item short form health survey (SF-36) and the short-form of Oral Health Impact Profile (OHIP-14). Results The mean score of sum OHIP-14 was significantly higher in the patients with OMD (10.81 ± 9.01) compared with those in the healthy subjects (HS) (6.55 ± 6.73) (p < 0.001, Mann-Whitney U test). 56.51% of the OMD patients and 12.94% of the HS reported at least one oral negative impact (p < 0.001, Chi-square test). The overall mean score of SF-36 was significantly lower in the patients with OMD (74.54 ± 12.77) compared with those in the HS (77.97 ± 12.39) (p = 0.021, t-test). Conclusions Administration of specific and generic questionnaires of QoL can provide us a detailed picture of the impact of OMDs on patients, and both generic and oral QoL were impaired in the patients with OMD.